Effects of conventional and biodegradable microplastics on a marine ecosystem engineer (Arenicola marina) and sediment nutrient cycling. (January 2016) - Green, Dannielle Senga; Boots, Bas; Sigwart, Julia; Jiang, Shan; Rocha, Carlos
Abstract: Effects of microplastic pollution on benthic organisms and ecosystem services provided by sedimentary habitats are largely unknown. An outdoor mesocosm experiment was done to realistically assess the effects of three different types of microplastic pollution (one biodegradable type; polylactic acid and two conventional types; polyethylene and polyvinylchloride) at increasing concentrations (0.02, 0.2 and 2% of wet sediment weight) on the health and biological activity of lugworms, Arenicola marina (Linnaeus, 1758), and on nitrogen cycling and primary productivity of the sediment they inhabit. After 31 days, A. marina produced less casts in sediments containing microplastics. Metabolic rates of A. marina increased, while microalgal biomass decreased at high concentrations, compared to sediments with low concentrations or without microplastics. Responses were strongest to polyvinylchloride, emphasising that different materials may have differential effects. Each material needs to be carefully evaluated in order to assess their risks as microplastic pollution. Overall, both conventional and biodegradable microplastics in sandy sediments can affect the health and behaviour of lugworms and directly or indirectly reduce primary productivity of these habitats. Graphical abstract: Highlights: Effects of conventional and biodegradable microplastics on lugworm habitats. 0.2–2% microplastics (by weight) reduced microalgal biomass of sediment. Biodegradable (PLA) and conventional (HDPE, PVC) microplastics had similar effects. High doses (2% by sediment weight) of PVC altered metabolism of lugworms. Microplastics altered burrowing activity of lugworms measured as casts. Abstract : Biodegradable and conventional microplastics altered activities of a key marine ecosystem engineer and reduced primary productivity of sandy sediments.